Arvoredol—An unusual chlorinated and biofilm inhibiting polyketide from a marine Penicillium sp. of the Brazilian coast. (June 2017) - Scopel, Marina; Mothes, Beatriz; Lerner, Clea B.; Henriques, Amélia T.; Macedo, Alexandre J.; Abraham, Wolf-Rainer
Graphical abstract: Highlights: A Penicillium sp. has been isolated from the marine sponge Axinella corrugata . Arvoredol, a chlorinated polyketide from this isolate is described. Arvoredol inhibits biofilm formation of the pathogen Staphylococcus epidermidis . Abstract: Penicillium sp. F37 has been isolated from the marine sponge Axinella corrugata and shown to be closely related to Penicillium maximae . From the culture of Penicillium sp. F37 arvoredol, a novel chlorinated polyketide with 6, 7-dihydro-4(5H)-benzofuranone moiety has been isolated and characterized by spectroscopic methods Arvoredol prevented biofilm formation of the human pathogen Staphylococcus epidermidis at a concentration of 125 μg mL −1 by 40%. It was also active against colorectal carcinoma HCT116 cells with a MIC of 7.9 μg mL −1 .